Genetic resistance to diseases and other stresses in improvement of ruminant livestock in the tropics - Baker, R.L.; Rege, J.E.O. (7th World Congress on Genetics Applied to Livestock Production, 1994)
Sustainable livestock improvement cannot be guaranteed for most tropical areas of the world without utilization of the evolutionary adaptation of the indigenous livestock breeds. The paper summarizes the adaptive traits of indigenous tropical breeds, presents a case for their evaluation and discusses the potential for exploiting inherent resistance to tolerance to biotic and abiotic stresses for genetic improvement of livestock in the tropics.